2015
DOI: 10.1186/s12876-015-0384-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between HER2 status in gastric cancer and clinicopathological features: a retrospective study using whole-tissue sections

Abstract: BackgroundGastric cancer is usually diagnosed in an advanced stage of disease and treatment options are sparse. Trastuzumab was recently approved for metastatic or locally advanced carcinomas arising in the stomach or in the gastroesophageal junction in patients with HER2-positive tumors. However, data on the frequency of HER2-positive cases among Brazilian patients are limited. Our aim was to characterize HER2 protein and gene status in a series of Brazilian patients with gastric cancer and to evaluate its as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
2
13
2
2
Order By: Relevance
“…SUV max was significantly lower in the HER2-positive group than in the HER2-negative group. Our data also demonstrated that HER2 expression is more common in well-or moderately differentiated adenocarcinoma than in poorly differentiated adenocarcinoma; this finding is consistent with the findings of previous studies (20)(21)(22). In addition, well-or moderately differentiated adenocarcinoma had significantly lower 18 F-FDG uptake than did poorly differentiated adenocarcinoma, partly explaining why patients with HER2 expression had a low SUV max (excluding signet-ring cell carcinoma from the analysis).…”
Section: Discussionsupporting
confidence: 92%
“…SUV max was significantly lower in the HER2-positive group than in the HER2-negative group. Our data also demonstrated that HER2 expression is more common in well-or moderately differentiated adenocarcinoma than in poorly differentiated adenocarcinoma; this finding is consistent with the findings of previous studies (20)(21)(22). In addition, well-or moderately differentiated adenocarcinoma had significantly lower 18 F-FDG uptake than did poorly differentiated adenocarcinoma, partly explaining why patients with HER2 expression had a low SUV max (excluding signet-ring cell carcinoma from the analysis).…”
Section: Discussionsupporting
confidence: 92%
“…The HER-2 positivity rate in our study is 10.99% which was comparable to several other studies like those conducted by Laboisseire et al 13 The methodology adopted by Sekaran et al was similar to that of our study. 17 However, they reported positive results in 44.2%.…”
Section: Discussionsupporting
confidence: 91%
“…All the HER-2 positive cases in our study showed intestinal type of histology with significant correlation (p=0.025) similar to the studies conducted by Rajagopal et al 20 Few studies, like those conducted by Laboisseire et al showed that in addition to the intestinal type, few cases with mixed type of histology also showed HER-2 positivity. 13 Studies by Figueroa-Barojas et al, Sekaran et al revealed no correlation between the two (p>0.05). 17,22 In our study, 25% of the grade-I tumors and 14.29% of the grade-II tumors were HER-2 positive.…”
Section: Discussionmentioning
confidence: 89%
“…In that study, elevated carcinoembryonic antigen levels, pulmonary metastasis, and distant lymph node metastasis have also emerged as significant predictors. Laboissiere et al identified intestinal histological subtype, histologic grade, and the presence of lymphovascular invasion as significant predictors of HER-2 positivity in gastric cancer [12]. In a study from Japan, intestinal type, absence of peritoneal metastasis, and hepatic metastasis were significant independent factors related to HER-2 positivity [13].…”
Section: Discussionmentioning
confidence: 99%